State and Entrepreneurship: The Failure to Create A Bumiputera Commercial and Industrial Community (BCIC) in Penang, Malaysia - Azeem Fazwan Ahmad Farouk (Kajian Malaysia, 2012)
This study examines the failure of the Malaysian state to create a Bumiputera Commercial and Industrial Class (BCIC) in the northern state of Penang. While analysts have emphasised the utility of strong states in inventing the bourgeoisie, especially in light of the impressive economic performances of the East Asian newly industrialised economies (NIEs), recent attempts to bring about a BCIC in Penang were unsuccessful, illustrating the extent to which the processes of class formation lie outside the control of even a relatively powerful state. It is suggested that although the state continues to maintain control over a large part of the economy, it is being challenged by dominant societal interests that were able to assert their economic and political interests, thereby limiting the state's autonomy.